Intravascular lithotripsy in recurrent restenosis in underexpanded saphenous vein graft stent - M. Wańczura, Piotr; B. Stecko, Wojciech (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Calcified stenosis in saphenous vein grafts (SVG) constitute a challenge in coronary artery disease. The risk for restenosis is clearly higher. High pressure techniques are relatively infrequently used due to risk of calcified graft dissection or perforation with possible cardiac tamponade. In-stent restenosis (ISR) within the underexpanded stent could be a challenge especially if non-compliance balloons (NC) are ineffective. In such a situation intravascular lithotripsy (IVL) using available tools, dedicated to calcified lesions, could be an option [1]. IVL technique uses a balloon-mounted ultrasound source by emitting the sonic energy propagating through the fluid into the calcified vessel wall. Defragmentation of atherosclerotic plaque is an expected aftermath of lithotripsy. Although IVL is not approved in SVG, this kind of off-label treatment could be the only chance for undilatable underexpanded lesions, significantly limiting flow to a relatively large area of myocardium [2].